Secondary postpartum hemorrhage caused by subinvolution of the placental site - Sarmiento-Piña, Maira (2024)
Postpartum hemorrhage is a major cause of obstetric morbidity and mortality,being associated with hemorrhagic shock and risk of disseminated intravascularcoagulopathy. Primary postpartum hemorrhage occurs within 24 hours of deliveryand cases classified as secondary occur after 24 hours and up to 6 weeks postpartum.A rare cause of secondary postpartum hemorrhage is vascular subinvolution ofthe placental implantation site. The underlying pathophysiological mechanismis unknown. However, this condition is considered idiopathic and non-iatrogenicbecause of its process of occurrence and development. Without other secondarycauses of postpartum hemorrhage, this condition is characterized by prolongedand/or excessive uterine bleeding, which can lead to fulminant hemodynamiccollapse. The anatomopathological diagnosis is based on the finding of persistent,patent, large, dilated and partially thrombus-occluded myometrial arteries, whichare adjacent to normally involuted vessels. Hysterectomy is the treatment forcases of severe hemorrhage. The aim of the study is to present a case of secondarypostpartum hemorrhage caused by subinvolution of the placental site.